A New Normal: Young Men of Color, Trauma, and Engagement in Learning. Issue 144 (December 2014) - Van Thompson, Carlyle; Schwartz, Paul J.
Abstract : This chapter will center on the continuing impact of systemic and persistent educational trauma experienced by Black and Latino males and how trauma affects their current learning. The young men's counterstories from a phenomenological study and documentary are included.